2018
DOI: 10.1038/s41564-018-0262-z
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of the bacteria-killing type IV secretion system core complex from Xanthomonas citri

Abstract: Type IV secretion (T4S) systems form the most common and versatile class of secretion systems in bacteria, capable of injecting both proteins and DNAs into host cells. T4S systems are typically composed of 12 components that form two major assemblies: the inner membrane complex embedded in the inner membrane and the core complex embedded in both the inner and outer membranes. Here we present the 3.3 Å resolution cryo-electron microscopy model of the T4S system core complex from Xanthomonas citri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
147
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(157 citation statements)
references
References 40 publications
10
147
0
Order By: Relevance
“…Although different in size and shape, both T4SS showed an outer membrane complex (OMC) with a 14‐fold symmetry. The atomic structure of the OMC of the VirB T4SS from Xanthomonas citrii, which mediates bacterial killing, confirmed this 14‐fold symmetry, as reported Tiago R. Costa from Gabriel Waksman lab (Imperial College, London, UK; Sgro et al, ). Intriguingly, the fine structure of two different T4SS, solved in situ by cryo‐ET, shed different results.…”
Section: Structure and Function Of T3 T4 And T6sssupporting
confidence: 76%
“…Although different in size and shape, both T4SS showed an outer membrane complex (OMC) with a 14‐fold symmetry. The atomic structure of the OMC of the VirB T4SS from Xanthomonas citrii, which mediates bacterial killing, confirmed this 14‐fold symmetry, as reported Tiago R. Costa from Gabriel Waksman lab (Imperial College, London, UK; Sgro et al, ). Intriguingly, the fine structure of two different T4SS, solved in situ by cryo‐ET, shed different results.…”
Section: Structure and Function Of T3 T4 And T6sssupporting
confidence: 76%
“…Structural details for several IVA machines have furthered our understanding of how these systems function. Xanthomonas citri VirB/D-, Helicobacter pylori Cag-, and E. coli R388-encoded IVA secretion machine structures resolved by single-particle cryoelectron microscopy (cryo-EM) and X-ray crystallography revealed that the IVA secretion machines are composed of an outer membrane-associated core complex (OMCC) that includes a large periplasmic assembly of proteins that connects to the secretion channel in the outer membrane (9)(10)(11)(12)(13). The OMCC recruits integral inner membrane (IM) proteins that connect to a cytoplasmic complex.…”
mentioning
confidence: 99%
“…Having established the direct role of CsrA in the repression of the virB operon, we asked 171 whether the interbacterial killing efficiency of X. citri would be enhanced in a strain lacking 172 the 5'UTR B7 . We used a X. citri virB10-msfgfp TL translational fusion strain (Sgro et al 2018) in 173 order to assess the number of T4SSs that are present per cell (see Materials and Methods 174 and Figure 2b). In this strain, the periplasmic VirB10 component has been replaced by a 175…”
mentioning
confidence: 99%
“…VirB10-msfGFP chimera. Since each T4SS contains 14 copies of VirB10, assembled T4SSs can 176 be observed as fluorescent periplasmic foci and counted (Sgro et al 2018). Deleting the 177 5'UTR B7 in the X. citri virB10-msfgfp TL genetic background resulted in a 2.6-fold increase in 178 the number of fluorescent T4SS foci that were counted per cell ( Figure 2b).…”
mentioning
confidence: 99%
See 1 more Smart Citation